INTERNAL AUDITOR INDEPENDENCE UNDER CONFLICTS OF INTEREST AND RELATIONAL PRESSURE: A PHENOMENOLOGICAL STUDY - Arianti; Nur Khaerunnisa Zakir; Syarifah Fatimiyah; Alimuddin; Darwis Said (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to understand the experiences of internal auditors in maintaining independence in audit conflict of interest situations. The study uses a qualitative approach with a phenomenological method to explore the experiences of internal auditors when facing independence threats in the audit process. The research informants consisted of two internal auditors: an auditor who audited a colleague suspected of fraud and an auditor who faced audit pressure due to power relations within the organization. Data were collected through in-depth interviews and analyzed using Moustakas' phenomenological approach. The results show that auditor independence is not only interpreted as compliance with professional standards, but also as a moral responsibility and professional identity of the auditor. Threats to independence arise through relational closeness, social pressure, and power relations that give rise to internal conflicts in the audit process. Auditors strive to maintain objectivity through self-control, limiting personal interactions, and a commitment to professionalism and integrity. This study shows that auditor independence is a complex experience that simultaneously involves professional, emotional, social, and moral dimensions.